1985
DOI: 10.1111/j.1348-0421.1985.tb00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition and Shwartzman Activity of Lipopolysaccharides from Oral Bacteria

Abstract: The composition and the nature of the linkage of fatty acids and the Shwartzman activity of lipopolysaccharide (LPS) preparations derived from oral gram-negative bacteria including Bacteroides gingivalis, Bacteroides loesheii, Eikenella corrodens, Fusobacterium nucleatum, and Actinobacillus actinomycetemcomitans were examined. 3-Hydroxylated and nonhydroxy fatty acids of various chain lengths were found in all of the LPS preparations. All nonhydroxy fatty acids were found to be ester-bound, and part of the 3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…As no fragment ion peaks specific for the branch were detected, it is suggested that the branching site is separate from the carboxyl radical. Wollenweber et al (1980) detected 3-hydroxy-15-methy1-hexadecanoic acid (3-OH-ise-Cl7 :0) in the LPS from B. fiagilis and four other Bacteroides species, a report confirmed by other investigators (Kasper et al, 1983;Nair et al, 1983;Mashimo et al, 1985;Johne & Bryn, 1986). We have found these branched 3-hydroxy fatty acids in the LPS from oral Bacteroides species such as B. oralis ATCk 33269, B. loescheii ATCC 15930, B. intermedius ATCC 2561 1 and B. corporis ATCC 33457 (unpublished data).…”
mentioning
confidence: 67%
“…As no fragment ion peaks specific for the branch were detected, it is suggested that the branching site is separate from the carboxyl radical. Wollenweber et al (1980) detected 3-hydroxy-15-methy1-hexadecanoic acid (3-OH-ise-Cl7 :0) in the LPS from B. fiagilis and four other Bacteroides species, a report confirmed by other investigators (Kasper et al, 1983;Nair et al, 1983;Mashimo et al, 1985;Johne & Bryn, 1986). We have found these branched 3-hydroxy fatty acids in the LPS from oral Bacteroides species such as B. oralis ATCk 33269, B. loescheii ATCC 15930, B. intermedius ATCC 2561 1 and B. corporis ATCC 33457 (unpublished data).…”
mentioning
confidence: 67%
“…The LPS in the cell surface of Gram-negative bacteria have been acknowledged to play many biological roles, such as pyrogenicity, mitogenicity, immunogenicity, and macrophage activation of serum complement.4 8 They have also been implicated in the initiation and progression of Periodontitis. [18][19][20][21][22][23][24][25][26][27][28][29][30] In vitro studies on the reduction of the biological activities of LPS with mild alkali, sodium dodecylsulphate, and EDTA (ethylene diamine tetraacetic acid) had been previously carried out.…”
Section: Discussionmentioning
confidence: 99%
“…there have been intensive investigations of the chemistry and endotoxic activities of the LPS of oral Gram-negative bacteria (2,6,8,12,13,18,20). Among such studies, there have been few reports on the LPS of F. nucleatum, although F. nucleatum is one of the predominant species in the gingival pocket.…”
Section: Human Gingival Fibroblastsmentioning
confidence: 99%